11C‐PE2I and 18F‐Dopa PET for assessing progression rate in Parkinson's: A longitudinal study. Issue 1 (30th October 2017) - Li, Weihua; Lao‐Kaim, Nick P.; Roussakis, Andreas A.; Martín‐Bastida, Antonio; Valle‐Guzman, Natalie; Paul, Gesine; Loane, Clare; Widner, Håkan; Politis, Marios; Foltynie, Tom; Barker, Roger A.; Piccini, Paola
Abstract: Background: 18 F‐dopa PET measuring aromaticl ‐amino acid decarboxylase activity is regarded as the gold standard for evaluating dopaminergic function in Parkinson's disease. Radioligands for dopamine transporters are also used in clinical trials and for confirming PD diagnosis. Currently, it is not clear which imaging marker is more reliable for assessing clinical severity and rate of progression. The objective of this study was to directly compare 18 F‐dopa with the highly selective dopamine transporter radioligand 11 C‐PE2I for the assessment of motor severity and rate of progression in PD. Methods: Thirty‐three mild‐moderate PD patients underwent 18 F‐dopa and 11 C‐PE2I PET at baseline. Twenty‐three were followed up for 18.8 ± 3.4 months. Results: Standard multiple regression at baseline indicated that 11 C‐PE2I BPND predicted UPDRS‐III and bradykinesia‐rigidity scores ( P < 0.05), whereas 18 F‐dopa Ki did not make significant unique explanatory contributions. Voxel‐wise analysis showed negative correlations between 11 C‐PE2I BPND and motor severity across the whole striatum bilaterally. 18 F‐Dopa Ki clusters were restricted to the most affected putamen and caudate. Longitudinally, negative correlations were found between striatal Δ 11 C‐PE2I BPND, ΔUPDRS‐III, and Δbradykinesia‐rigidity, whereas no significant associations were found for Δ 18 F‐dopa Ki . One cluster in the most affected putamen was identified in the longitudinal voxel‐wise analysis showing a negative relationship between Δ 11 C‐PE2I BPND and Δbradykinesia‐rigidity. Conclusions: Striatal 11 C‐PE2I appears to show greater sensitivity for detecting differences in motor severity than 18 F‐dopa. Furthermore, dopamine transporter decline is closely associated with motor progression over time, whereas no such relationship was found with aromaticl ‐amino acid decarboxylase. 11 C‐PE2I may be more effective for evaluating the efficacy of neuroprotective treatments in PD. © 2017 International Parkinson and Movement Disorder Society